The feasibility of head motion tracking in helical CT: A step toward motion correction. Issue 4 (14th March 2013) - Kim, Jung‐Ha; Nuyts, Johan; Kuncic, Zdenka; Fulton, Roger
Abstract : Purpose: : To establish a practical and accurate motion tracking method for the development of rigid motion correction methods in helical x‐ray computed tomography (CT). Methods: : A commercially available optical motion tracking system provided 6 degrees of freedom pose measurements at 60 Hz. A 4 × 4 calibration matrix was determined to convert raw pose data acquired in tracker coordinates to a fixed CT coordinate system with origin at the isocenter of the scanner. Two calibration methods, absolute orientation (AO), and a new method based on image registration (IR), were compared by means of landmark analysis and correlation coefficient in phantom images coregistered using the derived motion transformations. Results: : Transformations calculated using the IR‐derived calibration matrix were found to be more accurate, with positional errors less than 0.5 mm (mean RMS), and highly correlated image voxel intensities. The AO‐derived calibration matrix yielded larger mean RMS positional errors (≃1.0 mm), and poorer correlation coefficients. Conclusions: : The authors have demonstrated the feasibility of accurate motion tracking for retrospective motion correction in helical CT. Their new IR‐based calibration method based on image registration and function minimization was simpler to perform and delivered more accurate calibration matrices. This technique is a useful tool for future work on rigid motion correction in helical CT and potentially also other imaging modalities.